Introduction to adaptive optics Robert K. Tyson. - Tyson, Robert K., 1948- (SPIE Press, 2000)
Adaptive optics systems and components have achieved a level of sophistication and simplicity that goes beyond traditional applications in astronomy and the military and into developments in medicine, manufacturing, and communications. This book was written for those interested in the multidisciplinary technology and those who need a broad-brush explanation without wading through thousands of journal articles. It follows the structure of a one-day tutorial taught by the author, including humor and sidebars of historical material.
Keywords: Optics, Adaptive.; Optical instruments.; Optical detectors.; Optical measurements.; Telescopes.; elektronické knihy; electronic books